A National Study of Racial–Ethnic Differences in COVID-19 Concerns Among Older Americans: Evidence From the Health and Retirement Study. (21st September 2021) - Lin, Zhiyong; Liu, Hui
Abstract: Objectives: Concerns about coronavirus disease 2019 (COVID-19) are an important emotional reaction to the pandemic and represent a key pandemic-related mental health outcome. We provide the first population-based evidence of racial–ethnic differences in COVID-19 concerns among older Americans during the COVID-19 outbreak. Methods: We analyzed data from the 2020 Health and Retirement Study COVID-19 project. The sample included 2, 879 respondents (aged 50 and older) who were interviewed from June to September 2020 and had completed measures on COVID-19 concerns and other key covariates. Ordinary least squares regression models were estimated to assess racial–ethnic differences in COVID-19 concerns. Formal mediation analysis was conducted to test potential mediating roles of exposures to COVID-19 risks, preexisting health status, and socioeconomic resources in accounting for racial–ethnic differences in COVID-19 concerns. Results: Non-Hispanic Black and Hispanic Americans showed significantly greater concerns about the COVID-19 pandemic than non-Hispanic White Americans. Racial–ethnic minority older adults also had higher proportions of knowing someone who had contracted or died from COVID-19 than White older adults. Unequal exposures to COVID-19 risks by race–ethnicity and, to a lesser degree, preexisting health inequalities accounted for only part of the racial–ethnic differences in COVID-19 concerns. Discussion: Our findings call for more research and policy interventions to lessen the disproportionate burden of COVID-19 experienced by older adults of racial–ethnic minority groups.